Digital Experiential Learning for Sustainable Horticulture and Landscape Management Education - Kee, Tris; Zhang, Hao (Sustainability, 2022)
During the COVID-19 pandemic, horticulture and landscape management programmes in higher education experienced a huge drawback because of the impossibility of organising field studies and conducting site research. To pursue a more sustainable method of teaching, immersive technology such as augmented reality (AR) and virtual reality (VR) has been increasingly adopted as an effective approach for multimodal experiential learning. This study examines student perceptions on the use of digital technology in team-based hybrid learning to achieve sustainability in tree management using data collected from students of horticulture and landscape management in a higher education institute in Hong Kong. Key theoretical principles on Kolb’s experiential learning cycle as an interactive process are discussed, followed by an empirical analysis of student survey results. This research deepens the understanding of how immersive technology enhances both environmental sustainability and learning innovation. The results demonstrate that innovative ideas in instructional methods such as ARVR simulation can enhance the environmental sustainability of how tree management can be conducted, promoting a more environmentally conscious, experiential, collaborative and digital learning experience in higher education.